Activity monitoring in professional soccer goalkeepers during training and match play. (2nd January 2020) - Moreno-Pérez, Victor; Malone, Shane; Sala-Pérez, Lluís; Lapuente-Sagarra, Manuel; Campos-Vazquez, Miguel Angel; Del Coso, Juan
ABSTRACT: The purpose of the present study was to quantify the external load of professional soccer goalkeepers. Twenty professional goalkeepers participated in the study. Data were classified according to the number of days before or after the match day (MD) as follows: MD-4, MD-3, MD-2, MD-1 for the sessions before the match, and MD+1 for the session after the match. The total running distance covered (TD), the high metabolic load (HMLD), the number of high metabolic load efforts (HMLE) were progressively reduced from MD-4 to MD-1 but the values of these variables were always inferior to MD (ES: -3.79 to −1.11). There was a tendency for a progressive reduction in the number of high-intensity accelerations (ACC) and decelerations (DEC) from MD-4 to MD-1 although the values of ACC/DEC were superior to MD (ES: 0.19 to 2.05). Overall, MD-2 was the day with the lowest external load. During training sessions, starter goalkeepers performed more TD (ES: 0.36) and more HMLE (ES: 0.29) than non-starters. External load was progressively decreased in the days before match play for goalkeepers which is reflective of appropriate recovery and preparation practices within the cohort analysed. However, habitual goalkeepers training has an excess of accelerations/decelerations and a lack of running actions performed at high metabolic loads.